Report on professional attachment with JK technology Pte Ltd. - Tan, Su-Lynn. (2009)
The purpose of this report is to give a description of my business training experience at JK Technology Pte Ltd. The job rotation plan increased my understanding of the work flow between different departments. Generally, I learnt how the different departments needed to communicate and complement one another to increase the efficiency as well as performance levels.